Application of AGV in the Production System at the PT. Adhikara Wiyasa Gani - Agus Siswoyo; Rodik Wahyu Indrawan; Abdul Azis Abdillah (Recent in Engineering Science and Technology, 2023)
This study aims to analyze the effectiveness and efficiency of applying AGV in the production system at the PT. Adhikara Wiyasa Gani. AGV is implemented as a means of transporting materials from the warehouse to the production line, as well as returning finished goods to the warehouse. The research method used was data collection through field observations, interviews with workers, and analysis of production data before and after using AGV. The research results show that the use of AGV can increase the effectiveness and efficiency of the production system. The time required for material delivery from the warehouse to the production line and the return of finished goods to the warehouse can be minimized, thereby speeding up production time. In addition, AGV can also reduce production costs by reducing labor costs and minimizing the risk of human error in shipping goods. In conclusion, the application of AGV can have a positive impact on the production system at the PT. Adhikara Wiyasa Gani. However, further research can be conducted to deepen the effectiveness and efficiency of AGV implementation in production systems in general.